Information technologies and subjective well-being: Does the internet raise material aspirations? - Steffen Lohmann (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
This paper examines whether access to modern information technologies, in particular the internet, has an impact on invididual positionality - meaning the degree to which subjective well-being is affected by income relative to others rather than absolute income. We provide empirical evidence that positionality and internet access are intertwined. Exploiting variation over time in a panel of European households, we find stated material aspirations to be significantly positively related to computer access in areas with advanced internet infrastructure. Furthermore, we report cross-sectional evidence from the World Values Survey suggesting an indirect negative effect of internet access on subjective well-being since people who regularly use the internet as a source of information derive less satisfaction from income. Together, the empirical findings highlight the importance of information sets for how individuals evaluate own living conditions relative to others and suggests a vital role for informational globalisation to affect positionality.
Keywords: D03; I31; 330; subjective well-being; positionality; relative income; informational globalisation